Structure of hydrated calcium carbonates: A first-principles study - Demichelis, Raffaella; Raiteri, Paolo; Gale, Julian (Elsevier Science BV, 2013)
The structures of both ikaite (CaCO3·6H2O) and monohydrocalcite (CaCO3·H2O) were computed at the PBE0 level of theory, using all electron Gaussian type basis sets. Correction for the long-range dispersion contribution was included for the oxygen–oxygen interactions by using an additive pairwise term with the atomic coefficients fitted against the calcite vs aragonite enthalpy difference. The potential chirality of monohydrocalcite is discussed, as well as the helical motifs created by the three-fold rototranslational axes parallel to the [001] direction. These elements represent a significant link between monohydrocalcite and vaterite, both appearing as intermediate species during CaCO3 crystallization from amorphous calcium carbonate. The hydrogen bond pattern, never fully discussed for monohydrocalcite, is here described and compared to the available experimental data. Both phases are characterized by the presence of hydrogen bonds of moderate to high strength. Water molecules in monohydrocalcite interact quite strongly with 2 View the MathML source units through such hydrogen bonds, whereas their interaction with each other is minor. On the contrary, water molecules in ikaite create a complex network of hydrogen bonds, where each water molecule is strongly hydrogen bonded to one View the MathML source anion and to one or two other water molecules.